2012
DOI: 10.1182/blood-2011-08-371831
|View full text |Cite
|
Sign up to set email alerts
|

The TLR-mediated response of plasmacytoid dendritic cells is positively regulated by estradiol in vivo through cell-intrinsic estrogen receptor α signaling

Abstract: Plasmacytoid dendritic cells (pDCs) produce large amounts of type I interferons (IFN-␣/␤) in response to viral or endogenous nucleic acids through activation of their endosomal Toll-like receptors (TLR-7and TLR-9). Enhanced TLR-7-mediated IFN-␣ production by pDCs in women, compared with men, has been reported, but whether sex hormones, such as estrogens, are involved in this sex-based difference is unknown. Here we show, in humanized mice, that the TLR-7-mediated response of human pDCs is increased in female h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
272
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 279 publications
(314 citation statements)
references
References 50 publications
(73 reference statements)
24
272
2
1
Order By: Relevance
“…Our data adds to previous reports on the influence of sex on production of IFNα by pDCs, demonstrating that also surface maturation markers are upregulated more in female pDCs (Berghöfer et al, 2006;Meier et al, 2009;Seillet et al, 2012Seillet et al, , 2013. The effect of sex on upregulation of especially CD40 but also CD86 was respectively mostly or partially explained by the rs179008 variant allele.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Our data adds to previous reports on the influence of sex on production of IFNα by pDCs, demonstrating that also surface maturation markers are upregulated more in female pDCs (Berghöfer et al, 2006;Meier et al, 2009;Seillet et al, 2012Seillet et al, , 2013. The effect of sex on upregulation of especially CD40 but also CD86 was respectively mostly or partially explained by the rs179008 variant allele.…”
Section: Discussionsupporting
confidence: 74%
“…Although previous studies found no evidence for incomplete or skewed X-inactivation this was recently challenged by Souyris and colleagues who reported that pDC express more TLR7 in females due to escape of X-inactivation (Schott et al, 2007a;Berghöfer et al, 2006;Souyris et al, 2018). Besides, TLR7 function may be enhanced by female hormones and/or enhanced expression of molecules downstream of TLR7 (Seillet et al, 2012(Seillet et al, , 2013Griesbeck et al, 2015). It remains unclear why possession of a heterozygous genotype offers an advantage when it comes to pDC maturation and reducing CHB risk.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been previously reported that estrogens enhance pDCs' immune responses after TLR-7/TLR-9 stimulation in mice [27]. In order to get a more powerful and easily detectable immune activation after administration of mtDNA, only female animals were included in our study.…”
Section: Oxidized Mtdna Is a More Potent In Vivo Activator Of Pdcs Thmentioning
confidence: 99%
“…Estrogen effects are mediated by estrogen receptors (ERs) ERa and ERb, which function as ligand-induced transcription factors (3). This regulatory action of estrogens on immune responses and autoimmunity are thought to be due to a direct action on immunocompetent cells of the innate and adaptive immune systems (4), which have been recently shown to functionally express ERs, particularly ERa (5)(6)(7)(8)(9)(10)(11). Alternatively, estrogens, through their ERs, may act on precursor cells to regulate the differentiation and functions of lymphoid and myeloid cells (12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%